Pemetaan Riset Akuntansi Zakat: Analisis Bibliometrik - Kiki Hardiansyah; Viya Fatwa Nurmalasari; Lisa Aslamiah; Najwa Rahmadina; Risma (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
This study aims to determine the extent of the development of zakat accounting research by reviewing various literature. This research is here to fill the gap in the bibliometric research of zakat, which is still very limited. The method used is qualitative with bibliometric analysis using VOSViewer. The results showed that 42 articles related to zakat accounting were published in international journals, spanning 2015-2022. These articles have been published regularly in the last eight years (2015-2022). The majority of articles were published in 2020, which was 13 articles or 29.55%. The years 2015 and 2018 were the fewest, namely only 1 article or 2.27%. The articles are written individually (single author) as well as collaboratively (multiple authors). The most frequently used method of qualitative research is qualitative-descriptive, with a total of 19 articles. Meanwhile, the quantitative method that is most often used is the quantitative method with linear regression analysis, as many as 2 articles. The International Journal of Financial Research became the most significant journal. In total there are 298 citations, with keywords that are often used are zakat accounting, trust, business zakat, information system, and economic sustainability.